Rebo Wekasan Module To Instill Religious Values, Tolerance, Love the Motherland - Nuriyawati Nuriyawati; Ketut Prasetyo; Ali Haidar (Universitas Negeri Surabaya, 2020)
This study aims to anticipate radicalism and terrorism by instilling religious, tolerance, love for the country that exist in rebo wekasan tradition through modules in learning activities on class VII MTs. Daruttaqwa Suci with validation of the Silabus, RPP, rebo wekasan tradition module, module testing. Testing the student questionnaire module with 25 questions (religious-10, tolerance-8, love for the country-7). The completeness of learning outcomes VII A2 and VII B2 using multiple choice has increased by 13, 09%, a difference of 9.41 (VII A2) and increase of 10, 64%, a difference of 10.44 (VII B2) so that modules is very effective in learning . Hypothesis non-parametric Kruskall Wallis a significant value of 0.000 if the P value <0.05 then H1 accepted, Ho is rejected, mean difference in value before and after being given the module. Based on the results of data analysis, learning the rebo wekasan tradition module in instilling religious, tolerance, love for the country on the material of the influence of social interaction on the formation of social institutions is effective in anticipating radicalism and terrorism.